Green hydrogen : a guide to policy making (International Renewable Energy Agency, 2020)
Hydrogen produced with renewable energy sources - or "green" hydrogen - has emerged as a key element to achieve net-zero emissions from heavy industry and transport. Along with net-zero commitments by growing numbers of governments, green hydrogen has started gaining momentum based on low-cost renewable electricity, ongoing technological improvements and the benefits of greater power-system flexibility. Hydrogen-based fuels previously attracted interest mainly as an alternative to shore up oil supply. However, green hydrogen, as opposed to the "grey" (fossil-based) or "blue" (hybrid) varieties, also help to boost renewables in the energy mix and decarbonise energy-intensive industries. This report from the International Renewable Energy Agency (IRENA) outlines the main barriers that inhibiting green hydrogen uptake and the policies needed to address these. It also offers insights on how to kickstart the green hydrogen sector as a key enabler of the energy transition at the national or regional level.
Keywords: Hydrogen as fuel.; elektronické knihy; electronic books